Konsep Keadilan bagi Korban Perempuan dalam Sistem Penegakan Hukum Pidana Ditinjau dari Perspektif Teori Kesetaraan Gender - Magdhalena Tasik Todingrara; Vivilia Agnata Mudi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Gender equality theory, which is a branch of gender studies, offers an in-depth view of how gender inequality can occur in various aspects of life, including in the legal system. In simple terms, this theory distinguishes between formal equality and substantive equality. This research aims to analyze gender equality theory which can be used as an analytical framework for understanding injustice for female victims in the criminal law enforcement system and the impact of gender injustice in the criminal law enforcement system on female victims. This research uses a type of normative research with a conceptual approach. The data source used comes from secondary data. The data collection method is carried out through documentation studies. This research shows that gender equality theory is a very relevant analytical framework for understanding the injustices experienced by female victims in the criminal law enforcement system. Gender injustice in the criminal law enforcement system has a broad and deep impact, not only on individual female victims but also on social, cultural and institutional structures.